UK Oil and Gas Industry: Risks and Risk Management - Pampaka, Martha (2013)
Oil and gas industry is a developing industry, which faces multiple risks. A brief review of the industry is presented, followed by an overview of the risk management. A literature review which includes empirical studies and theories is provided. The purpose of this paper is the identification and quantification of risks in oil and gas industry. Also the impact of the existing risk management on the performance and value of the firms is examined. The data for the research were collected from DataStream. The study focuses on UK companies which trade in London exchange. Time series analysis as well as a panel data analysis is conducted in order to test whether interest rates, exchange rates, market returns, oil and gas prices affecting the equity returns in oil and gas industry. A cross-sectional analysis using the same organizations took place to justify whether total risk management add value to the firm or if it affects the performance of the company. Also control variables were included in the analysis. Finally beta coefficients from the time series analysis were used to examine whether the company characteristics influence the impact of risk factors on oil and gas returns. The results of the study have similarities and differences with previous papers. Firstly, it appears that market returns and oil price returns increase stock returns and they are statistically significant. On the other hand interest rates, exchange rates and gas returns are insignificant and have a negative effect on equity returns. In future research more independent variables must be included in the model, since it is not possible to predict equity returns with only the factors mentioned here. Firm characteristics impact some of the beta coefficients. Finally total risk management affects positively firm performance when using previous applied model. However it does not affect Tobin’s Q. Total risk management may not add value to the firm due to several factors such as the lack of executive commitment to risk management, the fragmented risk management activities, the fact that risk management is historical and not predictive and finally corporate strategy, strategic planning and risk management do not follow the same line. Future research must test which of these problems are faced by the industry or specific companies. This may explain why the existing risk management does not affect the value and performance of the organization.